Implementation of Value Chain and Cooperative Performance: A Case of Twongere Umusaruro Wa Kawa Cooperative Kayonza District, Rwanda - Hagenimana, Eric; Njenga, Gitahi; Nyabera, Sammy (International Journal of Entrepreneurship and Project Management, 2024)
Purpose: In this study, the Twongere umusaruro wa kawa cooperative's value chain implementation and cooperative performance were analyzed. The general purpose of the research study was to evaluate the relationship between the value chain implementation on cooperative performance in the Twongere umusaruro wa kawa cooperative. The study based on value chain and human capital theories. Methodology: The study used a descriptive cross-sectional survey to learn about value chain operations, investigate value chain marketing activities, learn about value chain service, and discover the extent to which these activities affect cooperative performance in Rwanda's Kayonza District. The total population consisted of 170 value chain actors, all of whom were farmers and members of the cooperative. A sample of 119 surveys based on the Slovenian formula used. In this study, the proportional random sampling was used as the sampling method. A questionnaire based on moderately structured interviews used to collect the primary data. The results of the survey were compiled, codified, tabulated, and analyzed. Made a change to improve data accuracy for encoding. The encoded data then entered in Statistical package for Social Sciences version 25. The statistically apparent relationship between factors and cooperative performance was examined with the Qui Square independence test. . Findings: Based on the study results, it was found a meaningful relationship between gender and cooperative performance, service and cooperative performance because p-values associated with gender and service, respectively, were p=0.03 and p=0.00 and did not exceed the 5% significance level. The findings also exposed no significant relation between operations and cooperative performance and marketing and cooperative performance. The findings indicated that the level of significance was above 5% for the operations and marketing-related p=0.462 and p=0.122, respectively. According to the study, value chain operators in cooperatives should pay closer attention to service and gender because of their strong associations with cooperative performance. Value chain developers in operations and marketing should be committed to overcoming any obstacles that hinder the cooperative's performance and should collaborate closely with members and partners to strengthen operations and marketing efforts for the cooperative's sustainability. Unique Contribution to Theory, Practice and Policy: Further studies should conduct a thorough analysis in this area by taking into account many independent factors in different districts of the country or the region to clearly show how value chain activities affect cooperative performance and to examine the impact of such changes, research should also invest in collecting data from several cooperatives and various cooperative types.